Revisiting the finance and growth nexus: A deeper look at sectors and instruments - Robert Unger (Deutsche Bundesbank, 2018)
This paper investigates empirically whether the relation between finance and growth depends on a specific type of financing. I construct a novel panel data set for 34 high income countries over the time period from 1995 to 2014 based on financial accounts data. It allows distinguishing between the sectors that receive financing - households and corporates - as well as a variety of different financial instruments. For the household sector I find an inverted u-shaped relation that indicates that high levels of finance are negatively related to economic growth. In contrast, financing of corporates is largely neutral. Furthermore, when controlling for the sectoral allocation of financing, no specific instrument - e.g. bank credit or market financing, debt or equity financing - seems to be particularly harmful or beneficial for growth.
Keywords: C23; G10; G21; O11; O47; 330; banks; debt; economic growth; equity; finance; markets